The economics of digital tools in Kazakh agriculture - Ryskeldi, Olzhas; Shelomentseva, Valentina; Mirkovic, Milika (International Journal of Innovative Research and Scientific Studies, 2024)
The agricultural sector in Kazakhstan represents only 5.4% of the total Gross Domestic Product and consists of livestock and crop production. The agricultural industry's potential production is limited by outdated technology, inefficient work practices and a lack of digitization which accounts for a small portion of the economy's overall value. Modernising agricultural output and making investments profitable represent some of the crucial challenges. However, in this field, limited research has been done. There are no studies investigating the profitability and return on investment of digitalization. Therefore, this paper investigates six digital technologies and their economic effects: health management in beef production, dairy cow movement tracking, drone counting systems, crop parallel driving systems, telematics and soil moisture monitoring. The data for this paper are from our own field studies of more than 138 farms in various regions of Kazakhstan. The extracted data includes the type of technology, equipment, cost and added profit of the farm. The investment performance indicators (IPI) were evaluated based on this data. Studies reveal that the use of technology demonstrates the financial viability of the digitalization of agriculture. The IPI of different technologies provides important information and data for farmers when making decisions about increasing the scope of digitization. Furthermore, the findings provide valuable understanding of the agricultural output in the area and serve as a solid foundation for the Kazakhstani government to establish forthcoming policies.